 ×     #### Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Click to Chat

1800-1023-196

+91-120-4616500

CART 0

• 0

MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping
```
Prove that if sin theta (1+ sin theta) + cos theta (1+ cos theta) = x and sin theta (1- sin theta) + cos theta (1- cos theta) = y then x^2 - 2x - sin 2 theta = y^2 + 2y - sin 2 theta = 0

```
2 years ago

```							hi ananya, thanks for asking.let sin(theta)=s and cos(theta)=cx= s+s^2+c+c^2=s+c+1or 2x=2s+2c+2and x^2=s^2+c^2+1+2(sc+c+s)=2+2(sc+s+c)so, x^2 - 2x - sin 2 theta = 2sc – sin 2 theta =0 [becoz  sin 2 theta =2sin theta* cos theta]similarly, y=s+c – 1so, 2y=2s+2c – 2and y^2=2+2(sc-s-c)so, y^+2y= 2scor y^2 + 2y - sin 2 theta = 0
```
2 years ago
Think You Can Provide A Better Answer ?

## Other Related Questions on Trigonometry

View all Questions »  ### Course Features

• 731 Video Lectures
• Revision Notes
• Previous Year Papers
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Test paper with Video Solution  ### Course Features

• 31 Video Lectures
• Revision Notes
• Test paper with Video Solution
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Previous Year Exam Questions